The Role of Social Control Mechanisms in Reducing Mass Riots in Football Stadiums (Abhat Journal, 2025)
The study aimed to analyze the role of both formal and informal social control mechanisms in reducing crowd riots in football stadiums. It focused on a sample of 79 players from Arab clubs participating in the Arab Mini-Football Championship in Libya. Using a social survey method with a questionnaire, the study found that adherence to Islamic teachings, including promoting good and preventing harm, helps foster positive behaviors and reduce riots. It also highlighted the importance of traditions in instilling social values and improving conduct. The media's role in reducing tension was emphasized, particularly by avoiding provocative content and promoting tolerance. Additionally, the study stressed the need for well-equipped security personnel and effective security plans to maintain order. The study recommended increasing religious and social awareness among fans, launching media programs promoting respect, and training security personnel while enhancing cooperation among institutions to ensure a safe, stable sports environment.
Keywords: Social control; riots; football; customs and traditions; laws and legislation